Symposium “Linking social indicators across scales-Upscaling/downscaling: the state of the art and challenges ahead”, at the IALE European Congress, Manchester 9-13 September - Carvalho Ribeiro, Sónia (2014)
The symposium will highlight the importance of bridging indicators across scales so that local scale assessments can inform policy making at broader scales. It will present the state of the art in methodological approaches for upscaling and downscaling assessments namely of social indicators and discuss future methodological and conceptual research needs. Most studies on social indicators address analysis at a local scale but the need for cross scale governance of environmental resources call for broader scale analysis in order to inform policy making and the targeting and monitoring of environmental programs at different levels of governance. Social indicators include measures that reflect people’s preferences for particular features in a given area. Land cover datasets have been widely used both at local and European scales of analysis. However, land cover composition and structure vary depending on the scale. The aim is to explore the ways in which results from local or European scale of analysis can be upscaled and downscaled. A key focus will be on social indicators for landscape as tools to comprehensively inform policy making. These indicators are likely to include land cover datasets combined with contextual data. This symposium will bring together a set of both conceptual and methodological papers on upscaling and downscaling social indicators in order to likely enhance cross scale governance and policy coordination. It will be relevant to researchers and policy makers using social indicators for monitoring landscape change and informing policy.